Pathogenicity and environmental tolerance of commercial and UK native entomopathogenic nematodes (Steinernema and Heterorhabditis spp.) to the larvae of mosquitoes (Aedes aegypti and Ochlerotatus detritus). Issue 3 (3rd July 2021) - Edmunds, Cassandra; Wilding, Craig S.; Rae, Robbie
Abstract: Many vector mosquito species have evolved resistance to chemical insecticides and the search for novel biological control strategies warrants further attention. Entomopathogenic nematodes (EPNs) ( Heterorhabditis and Steinernema spp.) have been developed as biological control agents for use against agricultural pests but whether they could be used to control aquatic mosquito larvae warrants further research. We exposed Aedes aegypti and Ochlerotatus detritus larvae to commercially available ( Steinernema feltiae, S. carpocapsae, S. kraussei and Heterorhabditis bacteriophora ) and wild isolated ( S. affine and S. glaseri ) EPNs and monitored survival over 7 days. We also exposed EPNs to water with a range of salinities and pHs found in the marshland habitats of British mosquitoes. Ae. aegypti and O. detritus were killed by commercial EPNs, but wild strains were unable to kill Ae. aegypti yet did kill O. detritus. All EPNs were capable of tolerating a wide range of pHs but showed variable tolerance to different salinities. EPNs could be used as an alternative to chemical insecticides but target species and habitat may influence choice of EPN strain in control operations.